O espaço e o imaginário popular nos contos de Afonso Arinos - Silva, Bruna de Carvalho Teixeira (2008)
The master s thesis Space and people s imaginary in Afonso Arinos short stories has as main objective to identify and analyze space and people s imaginary of four short stories by Afonso Arinos: Assombramento , Feiticeira , Mão pelada , and A garupa . The thesis was methodologically divided into introduction, development, conclusion, and references. The development is divided into seven chapters: the first chapter tells about the intellectual life of Afonso Arinos; the second presents the author s work; the third contains a reflection on the short story theory; the fourth refers to the critical fortune of Afonso Arinos; the fifth presents Brazilian regionalisms; the sixth approaches the theories of space and people s imaginary and the seventh presents the analyzes and interpretations of the selected short stories. Among the authors chosen for the theoretical foundation there are Gaston Bachelard, Julio Cortaz, Ricardo Piglia, Edgar Alan Poe, Anton Tchekhov, Laura de Mello e Souza, Jean Delumeau, Osman Lins, Luís da Câmara Cascudo, Tristão de Ataíde, Alfredo Bosi, Afrânio Coutinho, and Gilberto Freyre. The research makes possible to analyze not only the presence of the regional environment of Minas Gerais and people s imaginary, but also the importance of Afonso Arinos as a pre-modernist regionalist writer and his contribution to Brazilian literature.